2015
DOI: 10.1016/j.rbmo.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Kit ligand decreases the incidence of apoptosis in cultured vitrified whole mouse ovaries

Abstract: To investigate the development of follicles and incidence of apoptosis in vitrified cultured mouse ovaries in the presence and absence of Kit ligand, 1-week-old mouse ovaries were cultured in the presence or absence of Kit ligand for 7 days. Development and function of ovarian follicles was evaluated by histology and hormonal analysis. Apoptosis assessment was conducted by analysis of DNA laddering, TdT (terminal deoxynucleotidyl transferase)-mediated dUDP nick-end-labelling and caspase-3/7 activity. The propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
1
Order By: Relevance
“…We have previously shown that the negative effect of vitrification after one‐step in vitro culture of whole mouse ovaries on the developmental of follicles within these tissues, and a significant decline in the percent of normal follicles was demonstrated in vitrified samples than the nonvitrified group . Otherwise, the results of the present study showed that, after the two‐step in vitro culture of vitrified mouse ovaries, the rates of isolated follicles development, oocyte maturation, fertilization and blastocyst formation was similar to nonvitrified once.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We have previously shown that the negative effect of vitrification after one‐step in vitro culture of whole mouse ovaries on the developmental of follicles within these tissues, and a significant decline in the percent of normal follicles was demonstrated in vitrified samples than the nonvitrified group . Otherwise, the results of the present study showed that, after the two‐step in vitro culture of vitrified mouse ovaries, the rates of isolated follicles development, oocyte maturation, fertilization and blastocyst formation was similar to nonvitrified once.…”
Section: Discussioncontrasting
confidence: 53%
“…Preantral follicles (140–150 μm in diameter) were mechanically isolated from in vitro ‐cultured ovaries ( n > 170 in each group) under stereomicroscope. Then, to evaluate the survival rate, the isolated preantral follicles ( n = 20 in each group) were stained with 0.4% trypan blue . The surviving follicles were not stained, damaged follicles were stained moderately, and degenerated follicles were stained blue.…”
Section: Methodsmentioning
confidence: 99%
“…Bo Zhai’s work showed that BMP-15 may prevent the apoptosis of cumulus cells in cooperation with CCL2 [ 77 ]. Kit ligand, also called stem cell factor, is known to promote granulosa cell proliferation, and can function as an anti-apoptotic factor of follicle growth at different stages [ 80 , 81 ]. BMP-15 can stimulate KL expression in mammalian ovaries, and it seems that there exists a negative feedback loop between BMP-15 and KL while BMP-15 directly elevates the level of KL.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro culture (IVC) system of ovarian tissue is a considerably interesting alternative approach to improve the reproductive potential and preserve female fertility [1]. Many researchers have also been committed to de ning the optimal maturation condition (physical and biochemical condition) for the IVC system of ovarian tissue [2][3][4][5]. Despite the proposed designation of IVC systems, the improvement of this type of culture system is challenging because the survival rate of follicles, maturation rate of oocytes, and embryo development are still low compared with in vivo [6,7].…”
Section: Introductionmentioning
confidence: 99%